Dynamic pricing for inventories with reference price effects - Régis Chenavaz; Corina Paraschiv (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
This article presents a dynamic pricing model of a retailer selling an inventory, accounting for consumer behavior. The authors propose an optimal control model, maximizing the intertemporal profit with consumers sensitive to the selling price and to a reference price. The optimal dynamic pricing policy is solved with Pontryagin's maximum principle with a structural (general) demand function. The authors obtain an original pricing rule, which explicitly accounts for the impact of price and inventory on future profits. The dynamics of price do not have to imitate the dynamics of the reference price. Instead, the dynamics of price are tied to opposing effects linked to this reference price. The authors also discuss managerial implications with regards to behavioral pricing policies.
Keywords: C61; D03; D40; M21; M37; 330; Dynamic pricing; inventory; reference price; behavioral pricing; optimal control